2022
DOI: 10.1155/2022/1356735
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Different Lithological Rocks: A Case Study of the Coal Measure Strata in the Eastern Margin of Ordos Basin, China

Abstract: In this paper, the mechanical behaviors of different lithological rocks of coal measure strata from Shanxi Formation in the eastern margin of the Ordos Basin, China, were investigated through uniaxial compression tests, and the deformation characteristics and failure modes of different lithological rocks were investigated. On this basis, the energy evolution of different lithology rocks was also discussed. The results show that there are obvious differences in the mechanical properties of different lithology r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…However, the transitional shale reservoirs in the research region are characterized by the alternating occurrence of shale, coal rock and tight sandstone, and the thickness of single layer is minor and the cumulative thickness of shale reservoirs is significant (Kuang et al, 2020). The difference of mechanical properties among lithologies is obvious, and the rock physical properties response mechanism in rock mechanics is complex (Xiong et al, 2022). Traditionally, statistical methods such as simple and multiple regression techniques were poor at predicting mechanical parameters, with an average relative error of roughly 38.45%.…”
Section: Introductionmentioning
confidence: 97%
“…However, the transitional shale reservoirs in the research region are characterized by the alternating occurrence of shale, coal rock and tight sandstone, and the thickness of single layer is minor and the cumulative thickness of shale reservoirs is significant (Kuang et al, 2020). The difference of mechanical properties among lithologies is obvious, and the rock physical properties response mechanism in rock mechanics is complex (Xiong et al, 2022). Traditionally, statistical methods such as simple and multiple regression techniques were poor at predicting mechanical parameters, with an average relative error of roughly 38.45%.…”
Section: Introductionmentioning
confidence: 97%
“…8−10 By comparing the uniaxial compressive strength and point load strength of coal measure rocks, disparities in the mechanical properties stemming from diverse lithologies have been revealed, and the failure modes and damage mechanisms within these rocks have been elucidated. 11,12 Furthermore, the influence of the occurrence environment (water, temperature, and other factors) on rock mechanical properties has attracted scholarly attention, and it was found that water can significantly diminish the strength parameters of coal measure rocks by absorbing and affecting the clay minerals in the rocks. Additionally, the seepage pressure substantially impacts the failure pattern and extent of damage within coal measure rocks under the action of water seepage.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis and research on the mechanical characteristics of coal measure rocks have focused on exploring the strength and failure modes of coal measure rocks and the influence of the occurrence environment on the mechanical properties of rocks. Many researchers have tested the mechanical parameters of coal measure rocks, including the uniaxial compressive strength and tensile strength and investigated the relationships between the mechanical parameters of coal measure rocks, and between their mechanical parameters and acoustic wave velocity. By comparing the uniaxial compressive strength and point load strength of coal measure rocks, disparities in the mechanical properties stemming from diverse lithologies have been revealed, and the failure modes and damage mechanisms within these rocks have been elucidated. , Furthermore, the influence of the occurrence environment (water, temperature, and other factors) on rock mechanical properties has attracted scholarly attention, and it was found that water can significantly diminish the strength parameters of coal measure rocks by absorbing and affecting the clay minerals in the rocks. Additionally, the seepage pressure substantially impacts the failure pattern and extent of damage within coal measure rocks under the action of water seepage. Moreover, the increase in temperature exerts a discernible effect on the coal measure rock strength, presenting an initial increase followed by a subsequent decrease.…”
Section: Introductionmentioning
confidence: 99%
“…AE technology is a widely used non-destructive testing method, which can be used to reflect the crack evolution characteristics of the specimen and provide a variety of instability precursor information. The complexity of the AE frequency is closely related to the fracture mode of the specimen (Xiong et al 2022), and previous research on the frequency domain has achieved many very significant results. analysed the AE signals at the key points of rock specimens with different water contents after application of the fast Fourier transform to the spectral characteristics of the peak amplitude of the three-dimensional map corresponding to the main frequency comparison and found that the corresponding relationship is as follows: low water content-high main frequency-low damage and high water content-low main frequency-high damage.…”
Section: Introductionmentioning
confidence: 99%